Masa Tanam Kacang Tanah (Arachis hypogaea L.) Berdasarkan Neraca Air di Kecamatan Kakas Barat - Veronica Ester Buge; Anni E. Tarore; Adeleyda M. Lumingkewas (COCOS, 2017)
ABSRTACTPeanut is one of the plants, especially food sources of protein, carbohydrates and vitamins.Objective to determine planting peanuts (Arachis hypogaea L.) based on water balance in theDistrict of West Kakas. Materials and equipment used are secondary data of rainfall andevapotranspiration taken in Tondano Geophysics station, as well as physical data of land anduses a computer. The method used in this research is secondary data in the form of a surveymethod that includes climate data of rainfall and evapotranspiration observationsGeophysics Station Tondano Winangun obtained from BMKG station. Soil physical dataretrieval in Minahasa District Land Board. Early planting peanuts based on the criteria ofFAO, 1978 which is the first dasarian October. The results of the water balance analysisavailable planting peanut plants in the District of West Kakas which is 270 days, starting atthe beginning of the rainy season (rainfall = 0,5ETP) in dasarian I to dasarian III fromOctober to June. That it can be done three times a year planting.Key Words : Planting time, Peanut, Water Balance, Climate, Rainfall